Research allocation management system (REALMS) - Sie, Abby Chiang Yong (Universiti Malaysia Sarawak, UNIMAS, 2005)
Research Allocation Management System (REALMS) is a dynamic web-based research management system. It is developed to assist the administrative staffs, research coordinator and research members of the Faculty of Computer Science and Information Technology (FCSIT) in managing and facilitating the research project information available in the faculty. Besides that, the web-based application will also assist research coordinator and research members in obtaining the right information easily and effectively. REALMS is developed using Hypertext Pre-Processing language (PHP), JavaScript, Cascading Style Sheet (CSS) and Hypertext Mark-up Language (HTML). The system is run using the Open Source APACHIE web server together with MySQL database.